Water management and smallholder Fairtrade tea producers in South Western Uganda - Flowers, Cara (Cranfield University, 2007)
Kayonza growers’ tea factory is a remote tea factory in south western Uganda which consists of two core estates and 4072 smallholder tea farmers currently producing tea over a total area of 1604 hectares. There is a perception that yields of smallholder tea vary significantly throughout the year and between years. The data confirms this, with yields in the lowest producing months of February, July and August as little as 6% of annual yield production. Soil type also has an influence on yield with evidence suggesting that sandy loam soils suffer from more drought days than clay loam soils and generally have more uneven yields. The conceptual framework for analysis included a water balance model and a sustainable livelihoods framework. Methods of analysis included yield modelling, climate analysis and construction of a soil water balance model. Semi-structured in depth interviews with stakeholders formed the basis of sociological data collection. Soil water deficit modelling showed seasonal water deficits and a prolonged water deficit in 1999. Total available water was calculated to be 84 mm for clay loam soils and 42 mm for sandy loam soils. Yield analysis showed average yields of made tea to be 1250 kg ha-1 in 2005. However, yield prediction estimated possible yields of 2378 kg ha-1 of made tea. Yield patterns followed soil water deficits and correlated with rainfall patterns. Yield evenness may be affected by soil type differences in the Kayonza Growers Tea Factory area. Interviews with stakeholders supported observations on seasonal water stress and highlighted problems smallholders face accessing information and adequate inputs for tea production. Although tea provides a regular and reliable income source, smallholders may prefer to irrigate other high value cash crops and crops for home consumption. Individual water systems are likely to be used for domestic as well as agricultural use. Options for soil water conservation and small scale irrigation were explored in light of research findings. Soil water conservation measures, rainwater harvesting and treadle pump water management solutions are recommended for further investigation and piloting. Further analysis of yield and climate data would enable a finer grained understanding of geographical differences in tea yields. Investigation of factors affecting tea production such as labour time and shamba size may help to elucidate how smallholders manage tea production.